Effects Of Mastery Learning Strategy On Changing The Attitude Of The Students Towards Mathematics Among Secondary School Students In Machakos County, Kenya - Mulungye, Mary; Embeywa, Henry; Ogogo, Collins (MACHAKOS UNIVERSITY: THEME PROMOTING SUSTAINABLE DEVELOPMENT THROUGH DISRUPTIVE RESEARCH AND INNOVATION, 2022)
Mathematics is considered as a vital subject that supports the development of critical and logical thinking. It provides effective power to analyze, describe and understand the sciences hence fundamental subject in the school curriculum globally as an instrument for the development of all other sciences. However, majority of students across the world dislike mathematics and stay away from many careers related to mathematics. The students’ lack of interest for mathematics could be attributed to poor quality of instruction and the instructional method deployed but not lack of student’s ability to learn. The objective of the study was to investigate the impact of mastery learning strategy on changing the attitude of the students towards mathematics in Kenyan secondary schools located in Machakos sub-county. To achieve the objective a sample of one hundred and fifty four (154) form two students from two schools were randomly placed into either the group taught by using Mastery Learning Strategy (MLS), the experimental group or those taught using Conventional Group Learning (CGL), the control group. The two groups were subjected to an attitudinal test towards mathematics before and after the intervention of MLS. The Chi-Square and Z scores test statistics were used to test whether the two groups’ level of attitude towards mathematics differed significantly at   0.05 significance level. The attitudinal test showed that 36.4% of the students from the experimental group had a negative attitude towards mathematics compared to 58.3% of students from the control group. The computed z score value of |-2.72|was greater than the critical value of z = 1.96 at 5% level of significance, therefore the proportion difference between the two groups was statistically significant. The Chi-Square test confirmed the two groups’ level of attitude towards mathematics differed significantly at 95% confidence level. Therefore the MLS was recommended for changed of attitude towards mathematics among the students. The study recommended a replication of the research to another region and respondents to ascertain the validity and reliability of the findings.
Keywords: Effect; Mastery Learning Approach; Attitude; Students